Criação judicial de direito: ascensão institucional do poder judiciário, discricionariedade judicial e parâmetros para uma teoria da decisão com base em normas abertas - Lima, Gabriel Meira Nóbrega de (2018)
In a phenomenon that is recognized as a world trend, there is an increasingly pronounced intervention of the Judiciary in the formatting of State directives. In Brazil it is no different. The brazilian Judiciary, especially its supreme court, the Federal Supreme Court, has gradually increased its importance in the national institutional setting, from a power erased in the authoritarian period of the military regime, to a position of centrality in the current Brazilian institutional life, after redemocratization, and almost three decades of the Federal Constitution of 1988. The present study has as its object the current role of the Brazilian Judiciary, which does not only subsume the notion of the "negative legislator", acting as active coparticipant in the construction / creation of the right, the legitimacy and possibility of rationalization of this new function, which is not adequate to the classic tripartition of Powers idealized by the exegetical positivism. In order to do so, we analyzed the factors that allowed the expansion of Judiciary power, as well as the existence or not of judicial discretion in law, admitting that there are situations in which the order does not provide a precise answer, the law is " unfinished, "narrowing the boundaries between the creation and interpretation of the standard and making the interpreter an active participant in the process of building the legal response. Therefore, recognizing that in certain situations it is not acceptable that there is a penalization of society due to the dysfunctional context of the political system, this paper aims to propose criteria of legitimacy to avoid that the exercise of the representative function of the Judiciary Power promotes openness to decisions endowed with arbiters and personal preferences of the judges, the decisionism, with deleterious effects to the democratic regime and to the Law itself. In order to do so, he carried out a bibliographical research on the thematic "judicial decision theories" in Brazilian and foreign authors, confronting them with decisions selected by the Federal Supreme Court in the last decade.